Expression of VSTM1-v2 Is Increased in Peripheral Blood Mononuclear Cells from Patients with Rheumatoid Arthritis and Is Correlated with Disease Activity - Wang, Dashan; Li, Yan; Liu, Yuan; He, Yan; Shi, Guixiu (PloS one, 2016)
Rheumatoid arthritis (RA) is a chronic, systematic autoimmune disease that mainly affects joints and bones. Although the precise etiology is still unknown, Th17 cell is being recognized as an important mediator in pathogenesis of RA. VSTM1-v2 is a novel cytokine which has recently been reported to promote the differentiation of Th17 cells. This study is performed to study whether VSTM1-v2 can be recognized as a biomarker of RA, and is correlated to IL-17 expression. We obtained peripheral blood mononuclear cells (PBMCs) from 40 patients with RA and 40 age- and sex-matched healthy controls by standard Ficoll-Paque Plus density centrifugation. The mRNA expression levels of VSTM1-v2 and IL-17A in PBMCs were detected by real time-PCR. Disease activity parameters of RA were measured by routine methods. Our results showed that VSTM1-v2 mRNA expression in PBMCs from RA patients was significantly increased in comparison of that in healthy individuals. The VSTM1-v2 mRNA expression level was positively correlated with IL-17A mRNA expression level, DAS28, CRP and ESR, but was not correlated to RF, Anti-CCP or ANA. VSTM1-v2 might be a biomarker of RA and a novel factor in the pathogenesis of RA.